Influencia de Cereus vargasianus Cárdenas y Brasiliopuntia sp. (Cactaceae: Arborescentes) en la Composición del BTEs Corredor Ribereño Pampas - Apurímac, Región Ayacucho - Suclli Montañez, Efrain (2025)
The floristic composition of seasonally dry tropical forests BTEs in Peruvian territory is very varied, given the particularity of the biotic and abiotic components that make up the northern coast, the south-central Andean area and the eastern Amazonian slope. These attributes determine a clearly dissimilar composition and structure in reference to the forest species. This is the case of the dry forest that makes up the Pampas – Apurímac riparian corridor located on the northeastern departmental border of the Ayacucho and Cusco regions; the presence of Cereus vargasianus and Brasiliopuntia sp., cacti with a tree-like habit and new records for the region, would reinforce the particularity of a type of composition and structure unique in flora species of the BTEs of the inter-Andean type and the tropical area in general. The evaluation on 1000 m2 plots resulted in interaction with 13 woody species: Anadenanthera colubrina, Eriotheca vargasii, Ceiba aff. boliviana, Pseudobombax aff. marginatum, Tabebuia roseoalba, Handroanthus chrysanthus, Morisonia flexuosa, Juanulloa parasítica, Curatella americana, Erythroxylum squamatum, Ipomoea pauciflora, Luehea paniculata and Croton sp1. which reaffirms the uniqueness and conservation value of this plant formation.